Third Five-Year Plan Madras State - Planning Commission (Planning Commission, 1961)
The outlay on the National Plan falls into three broad sectors according to the agencies which are responsible for the implementation of the various schemes covered by the Plan. The first one is the Central Sector made up of the major development works undertaken by the Central Government such as the installation of the new steel plants, heavy machinery plants, fertilizer units, coal mining schemes, oil exploration and refineries, improvements to major ports and railways, etc.
Government of Madras